Occult spinal dysraphism: lessons learned by retrospective analysis of 149 surgical cases about natural history, surgical indications, urodynamic testing, and intraoperative neurophysiological monitoring - Valentini, Laura Grazia; Selvaggio, Giorgio; Erbetta, Alessandra; Cordella, Roberto; Pecoraro, Maria Giovanna; Bova, Stefania; Boni, Eleonora; Beretta, Elena; Furlanetto, Marika (Child's nervous system, 2013)
Purpose Prophylactic surgery is indicated for lipoma of the filum, while it is still debated for the conus lipomas and more complex tethering malformations of the cord. Methods We retrospectively reviewed the preoperative and postoperative clinical histories and long-term outcomes of 149 operated patients (33 adults, 116 children). Intraoperative neurophysiological monitoring (NPM) was utilized since 1998. Their malformative lesions were reclassified following recent Pang’s embryological criteria for surgical complexity. In nine cases, the spinal tethering malformation was associated with an anorectal malformation (ARM) and in nine with a Chiari I malformation (CM1). Results One hundred nineteen (80 %) patients were symptomatic at the time of surgery, 66 (44 %) having presented with progressive preoperative deterioration. Postoperative surgery-related deterioration was observed in 6 % of the cases operated on under the intraoperative NPM control. Surgery did not improve any deficit, especially of sphincter functions, independently from the type of associated malformation (ARM, CM1). Urodynamic testing was a reliable predictor both in the preoperative and in the follow-up period of subsequent neurological deterioration. In the long-term follow-up, an increasing percentage of retethering was observed, especially concerning complex cases submitted to partial excision. The surgical risk increased with repeated operations. Conclusions This study demonstrates that the rate of the natural deterioration associated with a conservative approach is higher than in patients operated on prophylactically, if the operation is performed by a team with a special expertise. However, the first surgical procedure should be aimed at detethering the conus completely, with the aid of intraoperative NPM; even in expert hands, it is associated with a high risk of clinical deterioration. Based on these results, we are increasing the percentage of children to whom surgery is offered when still asymptomatic as well as the degree of the lipoma excision to prevent retethering. However, in cases of rethetering and subjects presenting in adult age, we suggest to consider for surgery only those symptomatic. Urodynamic testing and magnetic resonance imaging in prone position were, in our experience, the best tools for screening those patients at risk of symptomatic retethering.